Etika dalam Periklanan Menyeimbangkan Kreativitas dan Tanggung Jawab Sosial - Muhammad Yusuf Wibiseno; Daniel Handoko (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
Advertising is an important tool in marketing communications, where creativity plays a key role in attracting consumer attention and conveying messages. However, there is a social responsibility that advertisers must uphold to ensure that the messages conveyed are not only creative but also ethical and do not harm society. This journal explores how a balance between creativity and social responsibility can be achieved in advertising practice.